Jewish Ethics as Dialogue - Pava, M. author. aut Link
XII, 192 p.
Keywords: Blending the deep traditions of Jewish humanism with modern philosophical expressions, this book argues that Jewish values are not fixed propositions embedded in written form that can be easily handed off from one generation to the next.